The Data Dissemination Resistant Trust Management Scheme for Securing Vehicular Ad Hoc Networks - K, Premkumar; R, Baskaran (International Journal of Computer Sciences and Engineering, 2019)
To increased safety and efficiency of road transportation system have promoted automobile manufacturers to integrate wireless communications and networking into vehicles. VANETs have the potential to transform the way people travel through the creation of a safe, interoperable wireless communications network that includes cars, buses, traffic signals, cell phones, and other devices. Due to increasing reliance on communication, computing, and control technologies have become vulnerable to security threats in VANET. To provide the security in VANET by developing the new mechanism which is integrity(data trust), confidentiality, non-repudiation, access control, real-time operational constraints/demands, availability, and data dissemination technique. In our proposed system propose the novel scheme which is called as trust management scheme data dissemination in order to eavesdroppers with threshold based malicious node detection algorithm (TMD) for VANETs that is able to accurately detect and cope with malicious attacks and also evaluate the trustworthiness of both data and mobile nodes in VANETs. At first the data trust is evaluated based on the data sensed and collected from multiple vehicles; after that we evaluate the node trust in two dimensions, i.e., functional trust and recommendation trust. The functional trust is indicating how likely a node can fulfill its functionality. The recommendation trust is indicating how trustworthy the recommendations from a node for other nodes will be, respectively. Finally our experimental result shows our proposed trust management theme is applicable to a wide range of VANET applications to improve traffic safety, mobility, and environmental protection with enhanced trustworthiness.